TATA KELOLA TEKNOLOGI INFORMASI DOMAIN PENGELOLAAN PERMINTAAN LAYANAN DAN INSIDEN TI MENGGUKAN COBIT 5 - Arief Ichwani; Livia Hendri Sefira (Smart Education, 2026)
Abstract: IT Governance has an important role in improving service quality and achieving IT-based organizational goals. The application of IT is inseparable from problems and incidents that can disrupt the company's operations. Handling of service requests and IT incidents needs to be managed in order to have a good impact, provide optimal service and in the future be able to provide profits or profits for the company in accordance with company objectives, so it is necessary to assess the capability level to measure the company's capabilities in handling service requests and incidents IT is happening. INews television station is a company engaged in the field of television electronic media that applies IT to its activities. To assess the capability level of service requests and IT incidents, the COBIT 5 sub domain DSS02 (Manage Service Request and Incident) sub-domain was used. Based on the capability level assessment carried out, the DSS02 process capability on iNews is at level 1 (performed) with the most achieved rating and the target capability level is level 2 (managed). To achieve the capability level target, improvements are made consisting of completing documentation, the implementation process that is in accordance with the process settings and work products must be determined, controlled, and monitored appropriately. Keywords: IT Governance; DSS02; COBIT 5 Abstrak: Tatakelola Teknologi Informasi memiliki peranan penting dalam meningkatkan kualitas layanan dan mencapai tujuan organisasi yang berbasiskan TI. penerapan TI tidak terlepas dari masalah dan insiden yang dapat mengganggu operasional perusahaan. Penanganan permintaan layanan dan insiden TI perlu dikelola agar memiliki dampak yang baik, memberikan layanan yang optimal dan di masa depan dapat memberikan keuntungan atau laba untuk perusahaan sesuai dengan tujuan perusahaan, sehingga perlu dilakukan penilaian tingkat kapabilitas untuk menilai kemampuan perusahaan dalam menangani permintaan dan insiden layanan yang sedang terjadi. Stasiun televisi iNews adalah perusahaan yang bergerak di bidang media elektronik yang menerapkan TI untuk kegiatannya. Penilaian kapabilitas permintaan layanan dan insiden TI menggunakan framework COBIT 5 sub-domain DSS02 (Manage Service Request and Incident). Hasil dari Penelitian ini ditemukan level kapabilitas proses DSS02 di iNews berada level 1 (performed) dengan hampir semua atribut proses tercapai dan target level yang diingin dicapai adalah level 2 (managed). Rekomendasi perbaikan untuk mencapai target level kapabilitas yang diberikan berupa pelengkapan dokumentasi, pengimplementasian proses sesuai pengaturan proses dan work products harus ditetapkan, dikontrol, dan dimonitor secara tepat. Kata Kunci: Tatakelola Teknologi Informasi; DSS02; COBIT 5